143k views
0 votes
Can someone help me with this don't mind the bubble I got bored and filled it in

Can someone help me with this don't mind the bubble I got bored and filled it in-example-1
User ZaPlayer
by
5.7k points

1 Answer

2 votes

Answer:

The solution is (1, 1).

Explanation:

y = -2x + 3

y = 5x - 4

Substitute y = 5x - 4 in the first equation:

5x - 4 = -2x + 3

5x + 2x = 3 + 4

7x = 7

x = 1

Now substitute x = 1 in the first equation:

y = -2(1) + 3

y = -2 + 3

y = 1.

User JREN
by
5.5k points